Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Minyak Goreng Merek Bimoli Pada Deta Toko di Desa Senaken Kecamatan Tanah Grogot - Istiqomah Istiqomah; Achmad Syahruddin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The purpose of this study was to determine the effect of simultaneous and partial as well as the dominant variable of the marketing mix consisting of product (X1), price (X2), promotion (X3) and place variable (X4) on purchasing decisions (Y) in Deta Stores in the Village Senaken District of Tanah Grogot. The sample for this study were consumers or people who made purchases at Deta Stores from May 2022 to June 2022. Using an incidental sampling technique, the number of samples obtained was 50 people. Consumers who were the sample in this study were given a questionnaire consisting of 31 statements. Responses to the questionnaire were tested for validity and reliability prior to multiple linear regression analysis using the SPSS application. The results of testing the research instrument, namely the questionnaire, showed that 31 statement items were declared valid because r count > r table. In addition, all statements are reliable because the cronbach`s alpha value is 0.940 > 060. The regression equation obtained Y = -0.045+0.582X1+0.023X-0.167X3+0.562X4. The correlation coefficient value of 0.896 shows a very strong relationship between the marketing mix which consists of product (X1), price (X2), promotion (X3) and place (X4) and purchasing decisions (Y) at Deta Shop in Senaken Village, Tanah District Grogot. The coefficient of determination (R2) is 0.785, which means that the marketing mix which consists of product (X1), price (X2), promotion (X3) and place variable (X4) can explain the purchase decision at Shop Deta in Senaken Village, Tanah Grogot District of 78 .5%, while the remaining 21.5% is influenced by other factors not included in this study. Simultaneous testing shows that the value of F count > F table or 45.828 > 2.5787 so that it can be concluded that there is at least one of the sub-variables of the marketing mix (X) consisting of product (X1), price (X2), promotion (X3) and place (X4) has an effect on purchasing decisions (Y) at Store Deta in Senaken Village, Tanah Grogot District. Furthermore, testing was carried out with the calculated t value of each marketing mix sub-variable consisting of product (X1), price (X2), promotion (X3) and place (X4) each of 3.157; 0.237; 1.531 and 3.844 which when compared with the t table is 2.0141, the product (X1) and place (X4) have a significant effect on purchasing decisions (Y) in Deta Shop in Senaken Village, Tanah Grogot District because the value of t count > t table. Meanwhile, price (X2) and promotion (X3) have no significant effect on purchasing decisions (Y) in Deta Stores in Senaken Village, Tanah Grogot District, because t count < t table. The dominant variable that influences purchasing decisions (Y) in Shop Deta in Senaken Village, Tanah Grogot District is place (X4) because the t value is the highest.